Is potroom asthma due more to sulphur dioxide than fluoride? An inception cohort study in the Australian aluminium industry. Issue 10 (26th August 2010) - Abramson, Michael John; Benke, Geza Paul; Cui, Jisheng; de Klerk, Nicholas Hubert; Del Monaco, Anthony; Dennekamp, Martine; Fritschi, Lin; Musk, Arthur William; Sim, Malcolm Ross
Abstract : Objectives: Although an asthma-like syndrome has been recognised in aluminium smelter workers for over 70 years, the causal agent has been difficult to identify. Methods: An inception cohort study was conducted at two Australian aluminium smelters where 446 employees participated over a period of 9 years. Cumulative exposures between interviews were estimated from job histories using a task exposure matrix based on measurements in the smelters. Participants completed an MRC respiratory questionnaire, spirometry and methacholine challenge test. Data were analysed with generalised estimating equations to allow for repeated measurements of each participant. Results: Wheeze and chest tightness, the two symptoms most closely related to asthma, showed associations with occupational exposures. SO2 exposure was significantly associated with these symptoms, bronchial hyper-responsiveness (BHR) to methacholine (a feature of asthma), airflow limitation (reduced forced expiratory volume in 1 second/forced vital capacity ratio) and longitudinal decline in lung function. Fluoride exposure was associated with the same outcomes, but less strongly. Inhalable dust and the benzene soluble fraction (BSF) were associated with symptoms of asthma and BHR. Although many of the exposures were highly correlated, further modelling suggested that of the known respiratory irritants, SO2 was more likely than fluoride to be primarily responsible for the symptoms observed. Fluoride, inhalable dust and SO2 were the most important airborne contaminants associated with effects on lung function. Conclusions: The observed effects were detected at contaminant levels within occupational exposure standards, so further reductions are required, particularly in SO2 exposures.